Biomass-based carbon-supported iron phosphide nano-catalyst as well as preparation method and application thereof
By using waste grapefruit peel and phytic acid to prepare biomass-based carbon-laden iron phosphide nanocatalysts, the problems of toxic gas generation and poor stability during the preparation of metal phosphide catalysts are solved, and efficient and environmentally friendly ammonia synthesis is achieved.
Patent Information
- Application Number
- CN202411666544.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, the preparation process of metal phosphide catalysts has problems of toxic gas generation and poor stability, and the traditional synthesis ammonia process has high energy consumption and high pollution.
By using waste grapefruit peel as carbon material raw material and combining phytic acid as the phosphorus source, biomass-based carbon-based iron phosphide nanocatalyst (FeP/PGP) is prepared using electrocatalytic technology to achieve the goal of efficient synthesis of ammonia.
The catalyst exhibits stability, high ammonia yield and high selectivity at high voltages, avoiding the oxidation of phosphorus, and significantly improving the efficiency and environmental protection of synthesis of ammonia.
Smart Images

Figure CN119465241A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new electrocatalyst materials, and in particular to a biomass-based carbon-supported iron phosphide nanocatalyst and a preparation method and application thereof. Background Art
[0002] Ammonia plays a vital role in modern society. It is a basic chemical for the production of fertilizers, various commodities and specialty chemicals, and is also an effective hydrogen carrier with advantages such as high hydrogen content and easy liquefaction. Industrial ammonia is synthesized by the Haber-Bosch process, which has high reaction energy consumption and emits a large amount of greenhouse gases. Nitrates and nitrites are common pollutants in industrial and agricultural wastewater. From the perspective of environmental protection and energy, converting nitrates and nitrites in wastewater into high-value-added NH3 by green electrochemistry is a strategy that kills two birds with one stone and is considered to be a promising green ammonia production method. The development of highly selective and stable catalyst materials is the key to achieving electrocatalytic nitrite / nitrate to ammonia production.
[0003] Metal phosphides have excellent charge transfer properties and active sites with adjustable composition. They are widely used in catalytic reactions such as hydrogenation and water decomposition. The P element can regulate the activity of nitrogen oxides (NO x - ) and active hydrogen adsorption and promote active hydrogen transfer, thereby achieving the purpose of efficient generation of ammonia. In oxygen reduction reactions (such as hydrogen evolution and oxygen evolution reactions), the surface of metal phosphides is prone to oxidation and reduction processes, causing corrosion of the catalyst. According to research, under high potential, phosphides may be oxidized into phosphates, resulting in a decrease in catalyst performance.
[0004] Biomass is abundant, renewable, and inexpensive, and is an important and ideal raw material for the preparation of highly conductive carbon materials. If a large amount of waste biomass is not promptly processed in production and life, it will form stubborn solid waste, which seriously harms environmental health. It is undoubtedly of great significance to effectively transform waste biomass into usable resources and active materials through chemical methods, so that it can continue to create value, killing two birds with one stone.
[0005] However, the main method for preparing metal phosphides is through gas-solid reaction. One method is to directly phosphate using highly active phosphorus vapor produced by red phosphorus and diammonium hydrogen phosphate as the phosphorus source. However, this high-temperature reaction will produce highly flammable white phosphorus and toxic phosphine. Another method is to use phosphates, phosphites, polyoxometalates, etc. as phosphorus sources, which have the risk of PH3 toxicity and leakage, which is not conducive to environmental health.
[0006] Therefore, there is an urgent need to develop catalytic materials that can utilize biomass to achieve green substitution of phosphorus sources in the preparation of metal phosphides and can efficiently catalyze the synthesis of ammonia. Summary of the invention
[0007] In view of the difficulties in utilizing solid waste biomass materials in the prior art, the generation of a large amount of toxic gases in the preparation process of metal phosphides, the poor stability of metal phosphide catalysts, and the high energy consumption and high pollution of traditional synthetic ammonia processes, the present invention provides a biomass-based carbon-supported iron phosphide nanocatalyst and a preparation method and application thereof. The present invention aims to make full use of waste grapefruit peel biomass, improve the stability and conductivity of metal phosphide catalysts, use phytic acid as a phosphorus source to greenly synthesize metal phosphides, and solve the problems of high energy consumption and high pollution in traditional synthetic ammonia processes through electrocatalytic technology, so as to meet the technical and usage needs in actual production.
[0008] In the research on phosphorus source modification, the inventors found that phytic acid, as a natural, non-toxic, economical and readily available phosphorus-containing organic acid, is widely used in food, chemical, medical and other industries, and is an ideal phosphorus source alternative raw material.
[0009] The present invention makes full use of waste biomass materials, uses phytic acid as a phosphorus source, converts it into high-quality phosphorus-rich carbon material in situ, and effectively loads the metal phosphide catalyst in situ, thereby preparing a new metal phosphide material catalyst, and applies it to electrocatalytic synthesis of ammonia, thereby providing a new way to synthesize ammonia.
[0010] The first aspect of the present invention provides a biomass-based carbon-supported iron phosphide nanocatalyst, comprising a grapefruit peel carbon material and FeP nanoparticles supported on the grapefruit peel carbon material, wherein the loading amount of the FeP nanoparticles accounts for 5.78-12.93wt% of the mass of the total catalyst;
[0011] The biomass-based carbon-supported iron phosphide nanocatalyst is prepared by loading FeP nanoparticles onto a grapefruit peel carbon material, and the chemical formula thereof is FeP / PGP.
[0012] More preferably, the loading amount of the FeP nanoparticles is 6.54-8.33%; and the phosphorus source of the FeP nanoparticles is phytic acid.
[0013] Preferably, in the biomass-based carbon-supported iron phosphide nanocatalyst, the content of Fe accounts for 3.73-8.34wt% of the total weight of the nanocatalyst, the content of P accounts for 13.56-14.98wt% of the total weight of the nanocatalyst, the content of O accounts for 6.24-11.11wt% of the total weight of the nanocatalyst, and the balance is C.
[0014] Preferably, the carbon layer thickness of the grapefruit peel carbon material in the biomass-based carbon-supported iron phosphide nanocatalyst is 0.2-1.0 μm.
[0015] The second aspect of the present invention provides a method for preparing the biomass-based carbon-supported iron phosphide nanocatalyst, comprising the following steps:
[0016] 1) dispersing grapefruit peel powder in deionized water, adding an iron source precursor and a phosphorus source precursor, and stirring to obtain a uniform mixed solution;
[0017] 2) The mixed solution obtained in step 1) is dried in an oven, placed in a tube furnace, introduced with inert gas, and calcined to obtain the product.
[0018] Preferably, the iron source precursor includes at least one of ferric chloride, ferric nitrate, ferric sulfate and ferric chloride hexahydrate; the phosphorus source precursor is phytic acid; and the inert gas is argon or nitrogen.
[0019] Preferably, the mass ratio of the grapefruit peel powder, the iron source precursor, the phosphorus source precursor and deionized water is (0.8-1.5): (0.1-1): (3-10): (10-20).
[0020] Preferably, the oven drying temperature and time in step 2) are 70-120° C. and 6-24 h, respectively.
[0021] Preferably, the setting program of the tube furnace in step 2) is to increase the temperature to 600-900°C at a heating rate of 5-10°C / min and keep the temperature for 1-3h.
[0022] Preferably, in step 2), the calcined product can be washed with water until the washing water is neutral, and then dried at 50-80° C. for 6-24 h.
[0023] The preferred method for preparing the grapefruit peel powder comprises the following steps:
[0024] The discarded grapefruit peel is crushed into powder and put into a beaker, NaOH solution is added, stirred evenly, put into an oven for concentration, cooled to room temperature, HCl is added to adjust the pH, washed with deionized water, and then freeze-dried to obtain clean grapefruit peel biomass, and finally the clean grapefruit peel biomass is crushed and sieved to obtain grapefruit peel powder;
[0025] As further preferred, the method for preparing the grapefruit peel powder specifically comprises the following steps:
[0026] 10-50 g of discarded grapefruit peel was crushed into powder and put into a beaker, 100-500 mL of 0.1 M NaOH solution was added, stirred for 1-2 h until uniform, put into an oven, heated at 70-90 ° C for 10-12 h to concentrate, cooled to room temperature, 1 M HCl was added to adjust the pH to 6.8-7.2, washed with deionized water, and then freeze-dried for 12-36 h to obtain clean grapefruit peel biomass. Finally, the clean grapefruit peel biomass was crushed and passed through an 80-mesh sieve to obtain grapefruit peel powder.
[0027] The formation mechanism of the above FeP / PGP is:
[0028] During the carbon activation process, phytic acid will be moderately dehydrated to obtain organic carbon. Through the cross-linking effect between inositol and the grapefruit peel powder biochar matrix, the strength of the carbon skeleton is strengthened to ensure the doping of phosphorus-containing substances on the biochar. The molecular structure of phytic acid is an asymmetric six-carbon ring, rich in phosphate. 1 mol of phytic acid can produce 6 mol of phosphate after complete hydrolysis. It has a strong chelating ability and can produce a strong coordination effect with metal iron ions to form a phytic acid-iron cross-linked structure. The biomass-metal composite precursor with this cross-linked structure is converted into metal iron phosphide after high-temperature pyrolysis of phytic acid-iron, and is loaded on the biomass in situ in one step.
[0029] The third aspect of the present invention provides an application of the biomass-based carbon-supported iron phosphide nanocatalyst in electrocatalytic synthesis of ammonia from sodium nitrite (NaNO2).
[0030] Preferably, the electrocatalysis is carried out in an H-type electrolytic cell, with the biomass-based carbon-supported iron phosphide nanocatalyst as the working electrode, Ag / AgCl as the reference electrode, and Pt as the counter electrode.
[0031] As further preferred, the specific steps of the electrocatalysis are as follows:
[0032] 1) preparing the biomass-based carbon-supported iron phosphide nanocatalyst into a slurry and applying the slurry on a glassy carbon electrode as a working electrode;
[0033] 2) Dissolve NaNO2 in 1M NaOH solution to make the concentration of NaNO2 0.1M, and perform electrochemical electrolysis.
[0034] Preferably, the mass ratio of the biomass-based carbon-supported iron phosphide nanocatalyst to NaNO2 is (0.8-1.3): (10000-20000).
[0035] Preferably, the preparation steps of the slurry in step 1) are as follows: 1-10 mg of the biomass-based carbon-supported iron phosphide nanocatalyst is dissolved in a mixed solution of 0.1-0.5 mL of water and 0.1-1.0 mL of anhydrous ethanol, 10-80 μL of a perfluoronaphthol sulfonate membrane solution with a resin solid content of 5-10 wt% is added dropwise, and ultrasonicated for 0.5-1 h to obtain a slurry.
[0036] Preferably, the electrochemical electrolysis test is performed on the electrolysis system for 1 hour, and the performance index ammonia yield is tested according to the national standard "Determination of Ammonia Nitrogen in Water by Nessler's Reagent Spectrophotometry (HJ 535-2009)", and the Faraday efficiency is calculated. The electrolysis test is performed at a voltage of -0.2V to -0.7V vs. RHE. The results show that at a voltage of -0.5V, the ammonia yield reaches 354.92±10.46μmol·h-1 cm -2 , the Faraday efficiency reached 93.22±1.56%. It can be seen that the FeP / PGP nanocatalyst provided in the present application has the advantages of stability under high voltage, high ammonia yield and high selectivity in the application of synthetic ammonia due to its effective support of carbon materials, and can avoid the oxidation of phosphorus under high potential to a certain extent.
[0037] The present invention provides a biomass-based carbon-supported iron phosphide nanomaterial catalyst and a preparation method thereof, and the catalyst can be used as an electrocatalyst in ammonia synthesis process, having the following beneficial effects:
[0038] 1) The present invention uses waste biomass grapefruit peel as a raw material for carbon material, uses organic phytic acid solution as a phosphorus source, and iron salt as an iron source, and calcines in a tubular furnace under the protection of an argon atmosphere to directly obtain an FeP / PGP nanocatalyst in situ; the catalyst is tightly encapsulated with the carbon base, so that the catalyst presents a subcrystalline form, and the thickness of the carbon material layer is 0.2-1.0 μm; at the same time, the addition of phytic acid significantly enhances the defects of the grapefruit peel carbon material, which is conducive to the exposure of the FeP active site, and the use of phytic acid as a phosphorus source has a high phosphorus content, and the six phosphates on the phytic acid inositol have strong chelating ability, and are easy to produce a strong coordination effect with metal iron ions, thereby promoting the formation of iron phosphide;
[0039] 2) This method provides solutions and application value for solving the problems of treatment of difficult-to-degrade agricultural and forestry wastes and construction of cheap, green and efficient synthetic ammonia catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 Scanning electron microscope images of FeP / PGP prepared in Example 1 of the present invention at different magnifications;
[0041] Figure 2 Transmission electron microscope images of FeP / PGP prepared in Example 1 of the present invention at different magnifications;
[0042] Figure 3 This is the element mapping distribution diagram of FeP / PGP prepared in Example 1 of the present invention;
[0043] Figure 4 The X-ray diffraction pattern of FeP / PGP prepared in Example 1 of the present invention;
[0044] Figure 5 The X-ray photoelectron spectrum of FeP / PGP prepared in Example 1 of the present invention, wherein a is the full spectrum; b is the C1s fine spectrum; c is the Fe 2p fine spectrum; d is the P 2p fine spectrum;
[0045] Figure 6 This is the Raman spectrum of FeP / PGP prepared in Example 1 of the present invention;
[0046] Figure 7 This is a scanning electron microscope image of FeP / PGP prepared in Example 2 of the present invention;
[0047] Figure 8 This is the element mapping distribution diagram of FeP / PGP prepared in Example 2 of the present invention;
[0048] Fig. 9 The X-ray diffraction pattern of FeP / PGP prepared in Example 2 of the present invention;
[0049] Fig.10 The scanning electron microscope images of FeP / PGP prepared in Example 3 of the present invention at different magnifications;
[0050] Fig.11 This is the element mapping distribution diagram of FeP / PGP prepared in Example 3 of the present invention;
[0051] Fig.12 The X-ray diffraction pattern of FeP / PGP prepared in Example 3 of the present invention;
[0052] Fig.13 This is a scanning electron microscope image of FeP / PGP prepared in Example 4 of the present invention;
[0053] Fig.14 This is the element mapping distribution diagram of FeP / PGP prepared in Example 4 of the present invention;
[0054] Fig.15 This is a scanning electron microscope image of FeP / PGP prepared in Example 5 of the present invention;
[0055] Fig.16 This is the element mapping distribution diagram of FeP / PGP prepared in Example 5 of the present invention;
[0056] Fig.17 FeP / PGP prepared in Example 1 of the present invention reduces NO2 at different voltages - Faradaic efficiency and ammonia yield curve;
[0057] Fig.18 This is a graph of an 11-cycle electrolysis experiment of FeP / PGP prepared in Example 1 of the present invention at an optimal voltage;
[0058] Fig.19 FeP / PGP prepared in Example 2 of the present invention reduces NO2 at different voltages - Faradaic efficiency and ammonia yield curve;
[0059] Fig. 20 FeP / PGP prepared in Example 3 of the present invention reduces NO2 at different voltages -Faraday efficiency and ammonia yield curve.
[0060] Fig.21 This is a scanning electron microscope image of FeP / GP prepared in Comparative Example 1 of the present invention;
[0061] Fig. 22 This is the element mapping distribution diagram of FeP / GP prepared in Comparative Example 1 of the present invention;
[0062] Fig.23 FeP / GP prepared in comparative example 1 of the present invention reduces NO2 at different voltages - Faradaic efficiency and ammonia yield curve;
[0063] Fig.24 Scanning electron microscope images of FeP prepared in Comparative Example 2 of the present invention at different magnifications;
[0064] Fig.25 Element mapping distribution diagram of FeP prepared in Comparative Example 2 of the present invention;
[0065] Fig.26 FeP prepared in comparative example 2 of the present invention reduces NO2 at different voltages - Faradaic efficiency and ammonia yield curve;
[0066] Fig. 27 This is a graph of an 11-cycle electrolysis experiment of FeP prepared in Comparative Example 2 of the present invention at an optimum voltage;
[0067] Fig.28 The scanning electron microscope images of Fe / GP prepared in Comparative Example 3 of the present invention at different magnifications;
[0068] Fig.29 This is the element mapping distribution diagram of Fe / GP prepared in Comparative Example 3 of the present invention;
[0069] Fig.30 Fe / GP prepared in comparative example 3 of the present invention reduces NO2 at different voltages - Faraday efficiency and ammonia yield curve. DETAILED DESCRIPTION
[0070] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments and drawings. These embodiments are only used to illustrate the technical solution of the present invention in more detail and should not be construed as limiting the scope of protection of the present invention.
[0071] The specific experimental conditions not specified in the examples were based on conventional conditions or the conditions recommended by the reagent company; the reagents, consumables, etc. used in the following examples, unless otherwise specified, can be obtained through commercial channels.
[0072] Example 1
[0073] A biomass-based carbon-supported iron phosphide nanocatalyst is prepared according to the following steps:
[0074] 1) Pretreatment of waste pomelo peel: 20 g of waste pomelo peel was taken, crushed into powder and put into a beaker, 300 mL of 0.1 M NaOH solution was added, stirred for 1 h, and put into an oven after being stirred evenly, heated at 80 ° C for 12 h to concentrate, cooled to room temperature, adjusted the pH to 7.0 with 1 M HCl, and washed with deionized water at 5000 rpm for 5 min; the washed pomelo peel was freeze-dried for 24 h to collect clean pomelo peel biomass; the clean pomelo peel biomass was crushed with a grinder and passed through an 80-mesh sieve to obtain pomelo peel powder.
[0075] 2) Calcination of FeP / PGP nanocatalyst: Weigh 0.2g of dried grapefruit peel powder and disperse it in 2mL of deionized water, then add 0.1g of ferric chloride hexahydrate and 1g of phytic acid solution (50wt%), stir evenly, and place in an oven at 80℃ for 12h. After drying, the sample is placed in a porcelain boat and placed in a tube furnace at a heating rate of 10℃·min -1 , heat treated at 700℃ for 2h in argon atmosphere. After cooling to room temperature, the sample was washed with deionized water until the water was neutral. After washing, it was dried at 60℃ for 12h to obtain FeP / PGP nanocatalyst.
[0076] like Figure 1 As shown, scanning electron microscopy (SEM) characterization tests show that the catalyst materials are densely stacked in block or flake form, and the carbon layer thickness of the grapefruit peel carbon material is 0.8 μm.
[0077] like Figure 2 As shown, transmission electron microscopy (TEM) tests showed that the catalyst was composed of very thin nanosheet structures stacked together to form a bulk structure, which was consistent with the SEM results.
[0078] like Figure 3 As shown, the TEM element mapping distribution test shows that C, O, Fe, and P elements are evenly distributed in the selected material area, the content of Fe element is 5.37wt%, the content of P element is 14.68wt%, the content of O element is 6.24wt%, and the content of C element is 73.71wt%. The molar ratio of iron element to phosphorus element in FeP is 1:1, and P element is excessive. The mass percentage of Fe element is calculated according to the formula (wt Fe ×M FeP ) / M Fe The FeP loading was calculated to be 8.33 wt%, of which wtFe is the mass content of iron, M FeP is the relative molecular mass of FeP, M Fe is the relative atomic mass of Fe.
[0079] like Figure 4 As shown, X-ray diffraction (XRD) tests confirmed the formation of iron phosphide, and peaks consistent with the standard card appeared at 32.7°, 35.5° and 37.2°, corresponding to the (011), (120) and (111) crystal planes, respectively.
[0080] like Figure 5 As shown, X-ray photoelectron spectroscopy (XPS) was used to analyze it. As shown in Figure a, the material mainly has C1s peak (≈284.8eV), O 1s peak (≈533eV), P 2p peak (≈132eV) and Fe 2p peak (≈712eV), indicating that C, O, P and Fe elements exist in FeP / PGP. C 1s fine spectrum Figure 5 b can be fitted into three different peaks at 284.80 eV, 285.96 eV and 289.33 eV, corresponding to CC, COP and OC=O bonds respectively. Phosphorus is combined with carbon in the form of chemical bonds, indicating that phytic acid as a phosphorus source also has a doping effect on the carbon substrate. Figure 5 d The fitted P 2p fine spectrum includes three peaks of PO, PC and P-Fe. The peak at a binding energy of 133.71 eV corresponds to the PC bond, the peak at a binding energy of 134.56 eV corresponds to the PO bond, and the peak at a binding energy of 131.86 eV corresponds to the P 2p 1 / 2 The P-Fe bond further indicates that P-Fe is successfully loaded on the phosphorus-doped biomass carbon. The Fe 2p fine spectrum can be fitted to Fe-PO (712.27 eV), Fe 3+ 3 / 2 (713.72eV), Fe 2+ 1 / 2 (724.23 eV), the peaks at 716.78 eV and 726.55 eV correspond to satellite peaks, indicating that FeP is successfully doped into the carbon skeleton, which can effectively modify the electronic configuration of FeP / PGP and improve the conductivity of the material.
[0081] like Figure 6 As shown, it can be seen from the Raman spectrum that compared with the Fe / GP prepared by the above method without adding phytic acid, the PGP prepared by the above method using only phytic acid and grapefruit peel carbon material without adding iron-containing raw materials, and the pure grapefruit peel carbon material GP, the addition of phytic acid as a phosphorus source reduces the degree of graphitization of the carbon material and increases the carbon defects, which is beneficial to the exposure of the active sites of FeP / PGP.
[0082] Example 2
[0083] A biomass-based carbon-supported iron phosphide nanocatalyst is prepared according to the following steps:
[0084] 1) Pretreatment of waste grapefruit peel: Take 30g of waste grapefruit peel, crush it into powder and put it into a beaker, add 200mL of 0.1M NaOH solution, stir for 1.5h, stir evenly and put it into an oven, heat at 70℃ for 12h to concentrate, cool to room temperature, adjust pH to 7.0 with 1M HCl, wash with deionized water at 5000rpm for 5min; freeze-dry the washed grapefruit peel for 36h, and collect clean grapefruit peel biomass. The clean grapefruit peel biomass is crushed with a grinder and passed through an 80-mesh sieve to obtain grapefruit peel powder.
[0085] 2) Calcination of FeP / PGP nanocatalyst: Weigh 0.2g of dried grapefruit peel powder and disperse it in 2mL of deionized water, then add 0.15g of ferric chloride hexahydrate and 1.2g of phytic acid solution (50%), stir evenly, and place in a 90°C oven for drying for 12h. After drying, the sample was placed in a porcelain boat and placed in a tube furnace for heat treatment at 600°C for 2h under argon atmosphere, with a heating rate of 10°C·min -1 After cooling to room temperature, the sample was washed with deionized water until the water was neutral. After washing, it was dried at 60°C for 12h to obtain FeP / PGP nanocatalyst.
[0086] like Figure 7 As shown, SEM characterization tests show that the catalyst materials are densely stacked in block or flake form, and the thickness of the carbon layer of the grapefruit peel carbon material is 0.9 μm.
[0087] like Figure 8 As shown, the SEM element mapping distribution test shows that C, O, Fe, and P elements are evenly distributed in the selected material area, the content of Fe element is 5.03wt%, the content of P element is 14.98wt%, the content of O element is 7.54wt%, and the content of C element is 72.45wt%. The FeP loading is calculated according to the formula described in Example 1 based on the mass percentage of Fe element, and the loading amount is 7.08wt%.
[0088] like Fig. 9 As shown, XRD test showed that the catalyst had peaks at 32.7°, 35.5° and 37.2° that were consistent with the standard card, corresponding to the (011), (120) and (111) crystal planes, respectively, indicating that FeP was successfully generated and loaded on biochar.
[0089] Example 3
[0090] A biomass-based carbon-supported iron phosphide nanocatalyst is prepared according to the following steps:
[0091] 1) Pretreatment of waste grapefruit peel: Take 25g of waste grapefruit peel, crush it into powder and put it into a beaker, add 350mL of 0.1M NaOH solution, stir for 2h, stir evenly and put it into an oven, heat at 90℃ for 10h to concentrate, cool to room temperature, adjust pH to 7.0 with 1M HCl, wash with deionized water at 5000rpm for 5min; freeze-dry the washed grapefruit peel for 30h, and collect clean grapefruit peel biomass. Crush the clean grapefruit peel biomass with a grinder and pass through an 80-mesh sieve to obtain grapefruit peel powder.
[0092] 2) Calcination of FeP / PGP nanocatalyst: Weigh 0.2g of dried grapefruit peel powder and disperse it in 2mL of deionized water, then add 0.08g of ferric chloride hexahydrate and 1.5g of phytic acid solution (50%), stir evenly, and place in a 90℃ oven for drying for 12h. After drying, the sample was placed in a porcelain boat and placed in a tube furnace for heat treatment at 800℃ for 2.5h in an argon atmosphere, with a heating rate of 10℃·min -1 After cooling to room temperature, the sample was washed with deionized water until the water was neutral. After washing, it was dried at 60°C for 12h to obtain FeP / PGP nanocatalyst.
[0093] like Fig.10 As shown, SEM characterization tests show that the catalyst material is densely packed in a large number of blocks or sheets, and the carbon layer thickness of the grapefruit peel carbon material is 1.0 μm.
[0094] like Fig.11 As shown, the SEM element mapping distribution test shows that C, O, Fe, and P elements are evenly distributed in the selected material area, the content of Fe element is 4.22wt%, the content of P element is 15.54wt%, the content of O element is 8.67wt%, the content of C element is 71.57wt%, and the FeP loading is calculated according to the formula described in Example 1 with the mass percentage of Fe element as 6.54wt%.
[0095] like Fig.12 As shown, XRD test showed that the catalyst had peaks at 32.7°, 35.5° and 37.2° that were consistent with the standard card, corresponding to the (011), (120) and (111) crystal planes, respectively, indicating that FeP was successfully generated and loaded on biochar.
[0096] Example 4
[0097] A biomass-based carbon-supported iron phosphide nanocatalyst is prepared according to the following steps:
[0098] 1) Pretreatment of waste pomelo peels: Example 4 uses the same method as Example 1 to pretreat waste pomelo peels.
[0099] 2) Calcination of FeP / PGP nanocatalyst: Weigh 0.2g of dried grapefruit peel powder and disperse it in 2mL of deionized water, then add 0.04g of ferric chloride hexahydrate and 1.0g of phytic acid solution (50%), stir evenly, and place in an oven at 80°C for 12h. After drying, the sample was placed in a porcelain boat and placed in a tube furnace for heat treatment at 700°C for 2h under argon atmosphere, with a heating rate of 10°C min -1 After cooling to room temperature, the sample was washed with deionized water until the water was neutral. After washing, it was dried at 60°C for 12h to obtain FeP / PGP nanocatalyst.
[0100] like Fig.13 As shown, SEM characterization tests show that the catalyst material is densely packed in a large number of blocks or sheets, and the thickness of the carbon layer of the grapefruit peel carbon material is 0.4μm.
[0101] like Fig.14 As shown, the SEM element mapping distribution test shows that C, O, Fe, and P elements are evenly distributed in the selected material area, the content of Fe element is 3.73wt%, the content of P element is 13.56wt%, the content of O element is 7.86wt%, the content of C element is 74.85wt%, and the FeP loading is 5.78wt% calculated according to the formula described in Example 1 based on the mass percentage of Fe element.
[0102] Example 5
[0103] A biomass-based carbon-supported iron phosphide nanocatalyst is prepared according to the following steps:
[0104] 1) Pretreatment of waste pomelo peels: Example 5 uses the same method as Example 1 to pretreat waste pomelo peels.
[0105] 2) Calcination of FeP / PGP nanocatalyst: Weigh 0.2g of dried grapefruit peel powder and disperse it in 2mL of deionized water, then add 0.16g of ferric chloride hexahydrate and 1.0g of phytic acid solution (50%), stir evenly, and place in an oven at 80°C for 12h. After drying, the sample was placed in a porcelain boat and placed in a tube furnace for heat treatment at 700°C for 2h under argon atmosphere, with a heating rate of 10°C·min -1 After cooling to room temperature, the sample was washed with deionized water until the water was neutral. After washing, it was dried at 60°C for 12h to obtain FeP / PGP nanocatalyst.
[0106] like Fig.15 As shown, SEM characterization tests show that the catalyst material is densely packed in a large number of blocks or sheets, and the carbon layer thickness of the grapefruit peel carbon material is 0.3μm.
[0107] like Fig.16 As shown, the SEM element mapping distribution test shows that C, O, Fe, and P elements are evenly distributed in the selected material area, the content of Fe element is 8.34wt%, the content of P element is 14.72wt%, the content of O element is 11.11wt%, and the content of C element is 65.83wt%; the FeP loading is calculated according to the formula described in Example 1 based on the mass percentage of Fe element, and the loading amount is 12.93wt%.
[0108] Application Example 1
[0109] FeP / PGP nanocatalyst electrocatalyzes nitrite to synthesize ammonia and performance test:
[0110] 1) Preparation of slurry: Take 5 mg of the sample prepared in Example 1 and dissolve it in a mixed solution of 0.20 mL of water and 0.75 mL of anhydrous ethanol, add 50 μL of a perfluoronaphthol sulfonate membrane solution with a resin solid content of 5 wt%, and ultrasonicate at room temperature for 1 h to fully disperse it in the solution. Take 10 μL of the solution and add it dropwise onto a glassy carbon electrode, dry it under an infrared lamp, and then perform an electrochemical test.
[0111] 2) Performance test of electrocatalytic nitrite synthesis of ammonia:
[0112] Take 80mL of 0.1M NaNO2 solution (dissolved in 1M NaOH solution) in an H-type electrolytic cell, use Ag / AgCl as the reference electrode and Pt as the counter electrode, and perform 1h electrolysis test at -0.2V vs.RHE, -0.3V vs.RHE, -0.4V vs.RHE, -0.5V vs.RHE, -0.6V vs.RHE and -0.7V vs.RHE. After the reaction is completed, take 0.5mL of electrolyte into a 25mL colorimetric tube, dilute to 25mL with 1M NaOH, and add 1mL of sodium potassium tartrate solution (0.58g / mL) and potassium mercuric iodide (0.172g / mL) solution in turn. After standing for 15min, use a UV-visible absorption spectrometer to detect the absorbance at a wavelength of 420nm. According to the national standard "Water quality-Determination of ammonia nitrogen-Nessler's reagent spectrophotometry (HJ 535-2009)", a standard ammonia solution was used as a standard curve, and the ammonia yield and Faraday efficiency of the electrocatalytic system were obtained according to the sample test results.
[0113] like Fig.17As shown in the figure, the maximum Faraday efficiency of the FeP / PGP nanocatalyst electrocatalytic system reached 93.22% at a voltage of -0.5 V. The ammonia yield reached 449.16 μmol·h at a voltage of -0.7 V. -1 cm -2 , indicating that the prepared FeP / PGP nanomaterials have excellent catalytic performance in electrocatalytic nitrite synthesis of ammonia.
[0114] like Fig.18 As shown, the FeP / PGP nanocatalyst maintained good stability in 11 electrolysis cycle experiments at the optimal voltage of -0.5V, and had excellent electrocatalytic ammonia synthesis performance.
[0115] Application Example 2
[0116] FeP / PGP nanocatalyst electrocatalyzes nitrite to synthesize ammonia and performance test:
[0117] 1) Preparation of slurry: Take 5 mg of the sample prepared in Example 2 and dissolve it in a mixed solution of 0.20 mL of water and 0.75 mL of anhydrous ethanol, add 50 μL of a perfluoronaphthol sulfonate membrane solution with a resin solid content of 5 wt%, and ultrasonicate at room temperature for 1 h to fully disperse it in the solution. Take 10 μL of the solution and add it dropwise onto a glassy carbon electrode, dry it under an infrared lamp, and then perform an electrochemical test.
[0118] 2) Performance test of electrocatalytic nitrite synthesis of ammonia:
[0119] Application Example 2 uses the same method as Application Example 1 to electrocatalyze nitrite to synthesize ammonia and perform electrochemical detection.
[0120] like Fig.19 As shown in Figure 2, the maximum Faraday efficiency of the FeP / PGP nanocatalyst electrocatalytic system reached 90.72% at a voltage of -0.7 V, and the ammonia yield reached 403.47 μmol·h -1 cm -2 , indicating that the prepared FeP / PGP nanomaterials have excellent catalytic performance in electrocatalytic nitrite synthesis of ammonia.
[0121] Application Example 3
[0122] FeP / PGP nanocatalyst electrocatalyzes nitrite to synthesize ammonia and performance test:
[0123] 1) Preparation of slurry: Take 5 mg of the sample prepared in Example 3 and dissolve it in a mixed solution of 0.20 mL of water and 0.75 mL of anhydrous ethanol, add 50 μL of a perfluoronaphthol sulfonate membrane solution with a resin solid content of 5 wt%, and ultrasonicate at room temperature for 1 h to fully disperse the solution. Take 10 μL of the solution and add it dropwise to a glassy carbon electrode, dry it under an infrared lamp, and then perform an electrochemical test.
[0124] 2) Performance test of electrocatalytic nitrite synthesis of ammonia:
[0125] Application Example 3 uses the same method as Application Example 1 to electrocatalyze nitrite to synthesize ammonia and perform electrochemical detection.
[0126] like Fig. 20 As shown in the figure, the maximum Faraday efficiency of the FeP / PGP nanocatalyst electrocatalytic system reached 92.46% at a voltage of -0.6 V. The yield of ammonia reached 383.48 μmol·h at a voltage of -0.7 V. -1 cm -2 , indicating that the prepared FeP / PGP nanomaterials have excellent catalytic performance in electrocatalytic nitrite synthesis of ammonia.
[0127] Comparative Example 1
[0128] Preparation of FeP / GP catalyst and performance test of electrocatalytic nitrite synthesis of ammonia:
[0129] 1) Preparation of FeP / GP catalyst: 0.2 g of grapefruit peel powder prepared in Example 1, 0.1 g of ferric chloride hexahydrate and 1.0 g of sodium hypophosphite monohydrate were weighed and ground evenly in a mortar. Subsequently, the sample was placed in a porcelain boat and placed in a tube furnace for heat treatment at 700 °C for 2 h in an argon atmosphere at a heating rate of 10 °C min -1 After cooling to room temperature, the sample was washed with deionized water until the water was neutral. After washing, it was dried at 60°C for 12h to obtain the FeP / GP nanocatalyst.
[0130] 2) Performance test of electrocatalytic nitrite synthesis of ammonia:
[0131] Comparative Example 1 adopts the same method as Application Example 1 to prepare the slurry, electrocatalyze nitrite to synthesize ammonia, and perform electrochemical detection.
[0132] like Fig.21 As shown, the FeP / GP synthesized using sodium hypophosphite presents a block structure, with no obvious morphological difference from the FeP / PGP synthesized using phytic acid, and the carbon layer thickness of the grapefruit peel carbon material is 0.9 μm.
[0133] like Fig. 22As shown, the element mapping distribution test of FeP / GP shows that the C, O, Fe, and P elements are uniformly distributed in the selected material area, wherein the loading of FeP synthesized by this method is 10.34%, the content of Fe element is 6.67wt%, the content of P element is 7.84wt%, the content of O element is 10.25%, and the content of C element is 75.24wt%.
[0134] like Fig.23 As shown in the figure, the maximum Faraday efficiency of the FeP / GP nanocatalyst electrocatalytic system reached 85.76% at a voltage of -0.6 V. The yield of ammonia reached 367.58 μmol·h at a voltage of -0.7 V. -1 cm -2 Compared with the FeP / PGP formed by phytic acid in Application Example 1, the ammonia yield at -0.7V voltage decreased by 81.58μmol·h -1 cm -2 .
[0135] Comparative Example 2
[0136] Preparation of FeP catalyst and performance test of electrocatalytic nitrite synthesis of ammonia:
[0137] 1) Preparation of FeP catalyst: Weigh 0.1 g of ferric chloride hexahydrate and 1 g of phytic acid solution (50%), stir evenly, and place in an oven at 80°C for 12 h. After drying, place the sample in a porcelain boat and place it in a tube furnace for heat treatment at 700°C for 2 h in an argon atmosphere with a heating rate of 10°C min -1 After cooling to room temperature, the sample was washed with deionized water until the water was neutral. After washing, it was dried at 60°C for 12h to obtain the FeP catalyst.
[0138] 2) Performance test of electrocatalytic nitrite synthesis of ammonia:
[0139] Comparative Example 2 uses the same method as Application Example 1 to prepare the slurry, electrocatalyze nitrite to synthesize ammonia, and perform electrochemical detection.
[0140] like Fig.24 As shown, SEM characterization shows that FeP presents a block structure.
[0141] like Fig.25 As shown, the element mapping distribution test of FeP shows that Fe and P elements are evenly distributed in the selected material area, wherein the content of Fe element is 49.67wt% and the content of P element is 50.33wt%.
[0142] like Fig.26As shown in the figure, the maximum Faraday efficiency of the FeP catalyst electrocatalytic system reached 80.32% at a voltage of -0.6 V. The ammonia yield reached 319.56 μmol·h at a voltage of -0.7 V. -1 cm -2 Compared with the FeP / PGP loaded with biochar in Application Example 1, the ammonia yield at -0.7 V decreased by 129.60 μmol·h -1 cm -2 , indicating that the loading of biochar improved the catalytic performance.
[0143] like Fig. 27 As shown, in the electrolysis experiment of FeP catalyst after 11 cycles at the optimal voltage of -0.6V, it can be observed that the ammonia yield and Faraday efficiency both decreased significantly in the 8th hour, indicating that the preparation of grapefruit peel biochar in the technical solution of the present application improved the stability of the catalyst.
[0144] Comparative Example 3
[0145] Preparation of Fe / GP catalyst and performance test of electrocatalytic nitrite synthesis of ammonia:
[0146] 1) Preparation of Fe / GP catalyst: 0.2 g of grapefruit peel powder prepared in Example 1 and 0.1 g of ferric chloride hexahydrate were weighed and ground evenly in a mortar. Then, the sample was placed in a porcelain boat and placed in a tube furnace for heat treatment at 700 °C for 2 h in a H2 / argon atmosphere at a heating rate of 10 °C min -1 After cooling to room temperature, the sample was washed with deionized water until the water was neutral. After washing, it was dried at 60°C for 12h to obtain the Fe / GP nanocatalyst.
[0147] 2) Performance test of electrocatalytic nitrite synthesis of ammonia:
[0148] Comparative Example 3 uses the same method as Application Example 1 to prepare the slurry, electrocatalyze nitrite to synthesize ammonia, and perform electrochemical detection.
[0149] like Fig.28 As shown, SEM characterization shows that Fe / GP presents a block structure.
[0150] like Fig.29 As shown, the element mapping distribution test of Fe / GP shows that Fe and C elements are evenly distributed in the selected material area, wherein the content of Fe element is 17.15wt% and the content of C element is 82.85wt%.
[0151] like Fig.30As shown in the figure, the maximum Faraday efficiency of the Fe / GP catalyst electrocatalytic system reached 60.49% at a voltage of -0.6 V. The ammonia yield reached 169.21 μmol·h at a voltage of -0.7 V. -1 cm -2 Compared with the FeP / PGP in Application Example 1, the ammonia yield at -0.7V decreased by 279.95μmol·h -1 cm -2 , indicating that the generation of metal iron phosphide in the technical solution of this application improves the catalytic performance.
[0152] In summary, the FeP / PGP obtained by the method provided by the present invention can be used as a catalyst in the electrocatalytic nitrate reduction ammonia synthesis process under normal temperature and pressure conditions, and has a significant catalytic effect and excellent cyclic catalytic stability.
[0153] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any equivalent substitutions, modifications, etc. made by technicians in this field without any creative work within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A biomass-based carbon-supported iron phosphide nanocatalyst, characterized in that: The catalyst comprises a grapefruit peel carbon material and FeP nanoparticles loaded on the grapefruit peel carbon material, wherein the loading amount of the FeP nanoparticles accounts for 5.78-12.93wt% of the total catalyst mass; and the phosphorus source of the FeP nanoparticles is phytic acid.
2. The biomass-based carbon-supported iron phosphide nanocatalyst according to claim 1, characterized in that: In the biomass-based carbon-supported iron phosphide nanocatalyst, the content of Fe accounts for 3.73-8.34wt% of the total weight of the nanocatalyst, the content of P accounts for 13.56-14.98wt% of the total weight of the nanocatalyst, the content of O accounts for 6.24-11.11wt% of the total weight of the nanocatalyst, and the balance is C.
3. The biomass-based carbon-supported iron phosphide nanocatalyst according to claim 1, characterized in that: The loading amount of the FeP nanoparticles is 6.54-8.33%, and the thickness of the carbon layer of the grapefruit peel carbon material in the biomass-based carbon-supported iron phosphide nanocatalyst is 0.2-1.0 μm.
4. The method for preparing the biomass-based carbon-supported iron phosphide nanocatalyst according to claims 1-3, characterized in that: The following steps are involved: 1) dispersing grapefruit peel powder in deionized water, adding an iron source precursor and a phosphorus source precursor, and stirring to obtain a uniform mixed solution; 2) The mixed solution obtained in step 1) is dried in an oven, placed in a tube furnace, introduced with inert gas, and calcined to obtain the product.
5. The method for preparing the biomass-based carbon-supported iron phosphide nanocatalyst according to claim 4, characterized in that: The iron source precursor includes at least one of ferric chloride, ferric nitrate, ferric sulfate and ferric chloride hexahydrate; the phosphorus source precursor is phytic acid; the inert gas is argon or nitrogen; the mass ratio of the grapefruit peel powder, the iron source precursor, the phosphorus source precursor and deionized water is (0.8-1.5): (0.1-1): (3-10): (10-20).
6. The method for preparing the biomass-based carbon-supported iron phosphide nanocatalyst according to claim 4, characterized in that: The oven drying temperature and time in step 2) are 70-120°C and 6-24h respectively; the setting program of the tubular furnace in step 2) is to increase the temperature to 600-900°C at a heating rate of 5-10°C / min and keep warm for 1-3h; in step 2), the calcined product is washed with water until the washing water is neutral, and dried at 50-80°C for 6-24h.
7. The method for preparing the biomass-based carbon-supported iron phosphide nanocatalyst according to claim 4, characterized in that: The preparation method of the pomelo peel powder comprises the following steps: crushing 10-50g of discarded pomelo peel into powder and putting it into a beaker, adding 100-500mL of 0.1M NaOH solution, stirring for 1-2h until uniform, putting it into an oven, heating at 70-90°C for 10-12h to concentrate, cooling to room temperature, adding 1M HCl to adjust the pH to 6.8-7.2, washing with deionized water, and then freeze-drying for 12-36h to obtain clean pomelo peel biomass, and finally crushing the clean pomelo peel biomass, passing through an 80-mesh sieve, and obtaining pomelo peel powder.
8. Use of the biomass-based carbon-supported iron phosphide nanocatalyst according to any one of claims 1 to 3 in electrocatalytic synthesis of ammonia from sodium nitrite.
9. The use of the biomass-based carbon-supported iron phosphide nanocatalyst in electrocatalytic sodium nitrite synthesis of ammonia according to claim 8, characterized in that: The electrocatalysis is carried out in an H-type electrolytic cell, with a biomass-based carbon-supported iron phosphide nanocatalyst as a working electrode, Ag / AgCl as a reference electrode, and Pt as a counter electrode.
10. The use of the biomass-based carbon-supported iron phosphide nanocatalyst in electrocatalytic sodium nitrite synthesis of ammonia according to claim 9, characterized in that: The specific steps of the electrocatalysis are as follows: 1) preparing the biomass-based carbon-supported iron phosphide nanocatalyst into a slurry and applying the slurry on a glassy carbon electrode as a working electrode; 2) dissolving NaNO2 in 1M NaOH solution to make the concentration of NaNO2 0.1M, and performing electrochemical electrolysis; The mass ratio of the biomass-based carbon-supported iron phosphide nanocatalyst to NaNO2 is (0.8-1.3): (10000-20000); The preparation steps of the slurry in step 1) are as follows: take 1-10 mg of the biomass-based carbon-supported iron phosphide nanocatalyst and dissolve it in a mixed solution of 0.1-0.5 mL of water and 0.1-1.0 mL of anhydrous ethanol, add 10-80 μL of a perfluorosulfonic acid naphthol membrane solution with a resin solid content of 5-10 wt%, and ultrasonicate for 0.5-1 h to obtain a slurry.
Citation Information
Cited By
Biomass-based carbon-supported ferronickel bimetallic phosphide catalyst as well as preparation method and application thereof
CN121781203A